ANALISIS KEBIJAKAN PENDIDIKAN TERKAIT KREDIBILITAS PENYELENGGARAAN UN-PBT DAN UN-CBT PADA TINGKAT SMA DAN MA - Sitti Nurlaela; Fitriani Fitriani; Nurawalia Nurawalia (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
The holding of two national examination systems namely the UN-PBT and UN-CBTmotivates to compare the strengths and weaknesses between the two, especially in relationtotheircredibility.Credibilityfornationalexamsmustbeplacedaboveallelseso that the objectives of the national exams are met as they should, especially in mathematics which are considered to have a high potential for dishonesty at the high schoolandMAlevels.-PBTandUN-CBTinhighschoolandMAmathematicssubjects